Persistent Neuroinflammation and Brain-Specific Immune Priming in a Novel Survival Model of Murine Pneumosepsis. Issue 1 (July 2020) - Denstaedt, Scott J.; Spencer-Segal, Joanna L.; Newstead, Michael; Laborc, Klaudia; Zeng, Xianying; Standiford, Theodore J.; Singer, Benjamin H.
Abstract : ABSTRACT: Pneumonia is the leading cause of sepsis and septic shock. Patients who survive pneumonia are vulnerable to long-term complications including increased risk of neurocognitive dysfunction. This study investigated the immune response and long-term complications of a non-surgical mouse model of Klebsiella pneumoniae pneumosepsis with antibiotic treatment. Pneumosepsis resulted in acutely enhanced expression of inflammatory cytokines, chemokines, and damage-associated molecular patterns in the brain and spleen. Despite resolution of infection, murine pneumosepsis survivors demonstrated a deficit in exploratory locomotor behavior at 2 weeks. This was associated with brain-specific persistent inflammatory gene expression and infiltrating myeloid cells in the brain. The brain inflammatory response was also primed in response to secondary challenge with lipopolysaccharide. The findings of this study demonstrate behavioral and inflammatory outcomes that parallel observations in other models of sepsis, but that have not previously been described in antibiotic-treated pneumonia models, highlighting a common pathway to the development of chronic brain dysfunction in sepsis survival. Abstract : Supplemental Digital Content is available in the text